MicroRNA-140-5p inhibits salivary adenoid cystic carcinoma progression and metastasis via targeting survivin - Zhu Qiao; Yue Zou; Hu Zhao (Cancer Cell International, 2019)
Abstract Background Salivary adenoid cystic carcinoma (SACC) is one of the most frequent carcinomas derived from the salivary gland. Growing evidence implied the involvement of microRNAs (miRNAs) in SACC progression and metastasis. This study aimed to determine the regulatory role of miR-140-5p in SACC progression and metastasis and to explore the underlying mechanisms. Materials and methods MiR-140-5p and survivin mRNA expression levels were determined by quantitative real-time PCR; protein levels were evaluated by western blot assay; cell proliferation, growth, invasion, apoptosis and caspase-3 activity were evaluated by respective in vitro functional assays; xenograft nude mice model was used to assess the in vivo tumor growth; a luciferase reporter assay determined the interaction between miR-140-5p and survivin. Results MiR-140-5p overexpression suppressed SACC cell proliferation and invasion, induced cell apoptosis and inhibited in vivo tumor growth of SACC cells. The loss-of-function studies showed that miR-140-5p knockdown enhanced SACC cell proliferation and invasion, inhibited cell apoptosis and led to an accelerated in vivo tumor growth. The bioinformatics prediction and luciferase reporter assay revealed that miR-140-5p directly targeted survivin 3′ untranslated region, and survivin was inversely regulated by miR-140-5p. Knockdown of survivin exerted tumor-suppressive effects on SACC cells, while enforced expression of survivin counteracted the tumor-suppressive actions of miR-140-5p overexpression in SACC cells. Mechanistically, miR-140-5p modulated the protein expression levels of apoptosis- and epithelial-mesenchymal transition-related mediators as well as matrix metallopeptidase-2/-9 via targeting survivin. More importantly, the down-regulation of miR-140-5p and the up-regulation of survivin were detected in the SACC clinical tissues, and miR-140-5 expression was inversely correlated with survivin mRNA expression level in SACC tissues. Conclusion Our data indicated that miR-140-5p suppressed SACC cell proliferation and invasion, induced cell apoptosis via regulating survivin expression. The present study provide evidence that that miR-140-5p could be a promising target for treating SACC, which requires further investigations.